Effect of adding Creatine and Methionine on Japanese Quails Performance - AL-Neemi, Mohammad Ibrahim; Ameen1, Qanaa Huassain; Mohammed, Mohammad Abdulraheem; Bahaal-deen, Mohammed Sabah (Sulaimani Journal for Pure and Applied Sciences, 2018)
The objective of this study was to evaluate the effect of creatine supplementation and additional plus 10% of the methionine requirement. All diets were isoenergetic and isonitrogenous and balanced with NRC recommendation. 336 ten day-old Japanese quail chicks unsexed were distributed according to a completely randomized experimental design into four treatments. Experimental treatments were :1) basal diet ( control ) , 2) basal diet + 6000 mg of creatine /kg feed , 3) basal diet + 1000 mg of additional methionine /kg feed and 4) basal diet + 6000 mg of creatine / kg feed and 1000 mg of additional methionine /kg feed. Each dietary treatment was designed to three replicate groups of 28 Japanese quail chicks and the experiment lasted 42 days. Birds were raised on litter and provided ad libitum access to both feed and water . chicks and feed were recorded to determine efficiency conversion ratio of feed , protein , energy , methionine and lysine . Inspected on a daily basis for mortality and mortality . During 42 days of the experiment , the body weight gain (BWG) , efficiency conversion ratio (ECR) for feed , protein , energy , methionine and lysine of chicks fed diets (treatments ) 2,3,and 4 were significance (P≤0.05) to that of birds fed control diet ( T1). On other hand there were no significant differences in the performance Traits among the 2,3 and 4 treatments.
Keywords: creatine; methionine; Japanese quail; diet and Performance